Implementation of the Value of Mutual Cooperation (Gotong Royong) through Night Patrol Activities in RT/RW 08/03, Kadudamas Village, Cirinten District, Lebak Regency - Komalasari, Siti Ainun; Suanto, Suanto (Universitas Pamulang, 2026)
This study examines the importance of awareness in implementing the value of mutual cooperation (gotong royong) through night patrol activities. Individual awareness plays a crucial role and needs to be continuously developed to strengthen community participation. This research was conducted in Kadudamas Village, RT/RW 08/03, Cirinten District, Lebak Regency. The objective of this study is to determine the level of community awareness in RT 08 in implementing the values of mutual cooperation in night patrol activities. This study employed a qualitative approach using data collection methods such as observation, interviews, and documentation. The findings reveal that the implementation of mutual cooperation values in night patrol activities among residents of RT 08 still needs improvement to ensure that all residents fulfill their responsibilities as good citizens. Although the level of awareness is generally considered good, it requires continuous enhancement through regular monthly evaluations. The efforts made by the head of RT 08 in fostering awareness and community spirit have been effective. For example, strict sanctions are applied to those who violate the rules, while appreciation and rewards are given to residents who are disciplined and active. These measures aim to strengthen awareness, encourage participation, and build a responsible and law-abiding community.